Four new species of Valvifera (Crustacea: Isopoda) from ANDEEP cruises in the Weddell Sea - Poore, Gary C. B.; Black, Jay R. (Zootaxa, 2024)
Four new species of Isopoda Valvifera are described from ANDEEP cruises in the Weddell Sea. They belong to three families: Fissarcturus brandtae sp. nov. and Fissarcturus polarsternae sp. nov. (Antarcturidae); Dolichiscus clarencensis sp. nov. (Austrarcturellidae); and Rectarcturus antarcticus sp. nov. (Rectarcturidae). Each new species is compared with others from the Southern Ocean. The species are illustrated using line drawings, microphotographs and micro-CT scans.